PENGARUH MODEL PROBLEM BASED LEARNING BERBANTUAN JEJARING SOSIAL GESCHOOL TERHADAP PEMAHAMAN KONSEP MATEMATIS PESERTA DIDIK KELAS IX SMPN 4 PADANG - Salsabila Yusfa (Departemen Matematika, 2021)
Understand mathematical concepts is one of the goals of learning mathematics which is expected to be mastered well by student. The reality in the field is that the understanding of mathematical concepts of class IX student at SMPN 4 Padang is still low. One of the efforts make to improve the ability to understand students’ mathematical concepts is to use the PBL model. The purpose of this research is to describe whether the understanding of mathematical concepts of students who learn to use Problem Based Learning model assisted by the geschool social network is preferable than the understanding of mathematical concepts of students who study use conventional learning models assisted by the geschool social network in class IX of SMPN 4 Padang. This type of research is a quasi-experimental design with a static group design. The population in this study were students of class IX SMPN 4 Padang in the academic year 2021/2022. Sample selection was done by random sampling technique, selected class IX.5 as experimental class and class IX.4 as control class. The instrument used is a test of understanding mathematical concepts in the form of description questions. The hypothesis test used is the t test. Based on the results of research data analysis at the real level = 0,05 using the t test, it obtained that the understand of mathematical concepts of students who learn used the Problem Based Learning model with the help of the geschool social network was better than the students who used the conventional learning model assisted by the geschool social network in the classroom IX SMPN 4 Padang. Keywords - understanding mathematical concepts, Problem Based Learning, conventional learning